State Responsibility in the Fulfillment of Public Health Rights through JKN: A Comparative Study with the Republic of China - Fitriyah, Dyah Kusumaning; Huda, Mokhamad Khoirul; Pramono, Budi (CV. Global Health Science Group, 2024)
The right to live with an adequate standard for the health and well-being of oneself and one's family is a human right recognized by all countries worldwide. Therefore, the state has a responsibility to provide proper healthcare to improve public health and the well-being of its citizens, where the implementation of social security is a prerequisite for a welfare state. Based on these circumstances, the following issues are formulated: 1) The regulation of the national health insurance system in Indonesia and the Republic of China; 2) The responsibilities of both countries in providing health protection through national health insurance. Objective to analyze the regulation of each national health insurance system in the Republic of China and Indonesia and analyze the legal efforts made by each country to protect its citizens to obtain welfare in terms of health insurance. This study is normative juridical research with a legislative approach, a conceptual approach, and a comparative approach. We employ a documentary study as a data collection method, involving primary, secondary, and tertiary sources related to the topic. Legal material analysis is conducted using a qualitative approach to address the research problems. This method produces descriptive-analytical data in the form of written, verbal, or actual behavior. The secondary data obtained through the documentary study will be analyzed concerning the applicable laws in both countries and compared accordingly. The findings of this thesis indicate that there are similarities and differences in the regulation of national health insurance in the two countries, particularly in terms of history, insurance providers, participation, covered services, and financing. Indonesia has fulfilled its constitutional obligation as stipulated in the 1945 Constitution and Law No. 40 of 2004 on the National Social Security System, which mandates the implementation of the Indonesian National Health Insurance to provide healthcare services for every citizen. Meanwhile, in the Republic of China (Taiwan), the National Health Insurance fulfills the constitutional obligations set forth in the Constitution of the Republic of China. The national health insurance systems in Taiwan and Indonesia have different approaches. Taiwan implements a centralized National Health Insurance, managed by the NHIA, with funding from individual contributions, employers, and government subsidies. In Indonesia, the National Health Insurance is managed by the Health Social Security Agency (Badan Penyelenggara Jaminan Sosial Kesehatan) under the Social Security Agency Act, despite facing accessibility and efficiency challenges. Both countries protect the health rights of their citizens through their respective legal bases. Taiwan relies on the Constitution of the Republic of China and National Health Insurance regulations, while Indonesia uses the 1945 Constitution and related regulations. To improve transparency, funding, and service quality, Indonesia can study Taiwan's National Health Insurance system and strengthen policy evaluation and public education.